UV acrylic optical bonding glue, preparation method thereof and composite optical film
By using acrylic oligomers, polyurethane oligomers, epoxy oligomers and other compositions, combined with photoinitiators and coupling agents, a low viscosity UV acrylic optical bonding glue was prepared, which solved the problem of poor adhesion of existing glue to the prism layer and the need for solvent dilution, and achieved efficient and environmentally friendly composite optical film bonding effect.
Patent Information
- Application Number
- CN202411750876.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing UV acrylic optical bonding glue has poor adhesion to the prism layer, resulting in weakening of the optical gain effect and requiring solvent dilution to achieve appropriate viscosity, increasing energy consumption and pollution.
A low viscosity UV acrylic acid optical bonding glue can be prepared by mixing three systems: acrylic oligomers, polyurethane oligomers, and epoxy oligomers, combined with photoinitiators and coupling agents, which can be directly applied to the composite optical film industry and have soft bonding performance, high tensile strength and excellent peeling force performance.
It achieves the effect of direct coating without solvent dilution, reduces energy consumption and pollution, and has better peeling force performance than existing glues, meeting the high-strength bonding needs of the composite optical film industry.
Smart Images

Figure CN119220206B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesives, and in particular to a UV acrylic optical bonding glue, a composite optical film and a preparation method thereof. Background Art
[0002] As display technology is moving towards extreme lightness and thinness, more stringent requirements are placed on the materials that make up the display. The backlight module in a traditional LED display is usually assembled manually from multiple independent optical films such as diffusion film, brightness enhancement film and reflective polarizer. These single-layer films often need to maintain a certain thickness to maintain the necessary stiffness. The stacking of multiple layers significantly increases the overall thickness, which seriously hinders the process of thinning the display. In view of this, the industry generally tends to adopt a composite optical film strategy that combines two or more functional films such as diffusion film and brightness enhancement film into an integrated structure, such as diffusion film-prism brightness enhancement film (DOP), prism brightness enhancement film stack (POP), microlens film-prism brightness enhancement film (MOP) and other composite structures. This not only greatly simplifies the assembly process, but also significantly reduces the overall thickness.
[0003] However, in the preparation process of composite optical films, the selection of efficient and environmentally friendly adhesives has become a major challenge. Currently, the high cost and high viscosity of bonding glue (usually more than 5000 mPa·s) limit direct application. It is necessary to add organic solvents to dilute it to a suitable viscosity to achieve roll-to-roll coating, thereby accurately controlling the coating thickness and appearance quality. In this process, the volatilization of solvents also increases additional heat energy consumption.
[0004] More importantly, the existing UV acrylic optical bonding glue has poor adhesion to the prism layer, and it is often necessary to increase the bonding width of the prism structure and the bonding layer (about 6-8μm) to enhance the peel strength, but this undoubtedly sacrifices the focusing efficiency of the prism, resulting in a weakened optical gain effect. Therefore, the development of a UV acrylic optical bonding glue that can be directly coated, has excellent adhesion properties, and has minimal impact on the prism structure has become a technical problem that needs to be solved urgently. This not only requires the glue to have a suitable viscosity range for direct coating operations, but also to form a thin and uniform (about 3μm) adhesive layer after curing, while ensuring a high adhesion to the prism layer, meeting the requirements of small dipping (about 4μm bonding width for the prism layer) and large peel strength, thereby ensuring minimal interference with the prism structure to maximize the retention of its optical properties. Summary of the invention
[0005] The purpose of this application is to provide a UV acrylic optical bonding glue, which has both soft bonding performance and high tensile strength and bonding strength, and has low viscosity, and can be directly used in the composite optical film industry. It does not need to be diluted with solvent before coating to achieve the required coating thickness and obtain a good appearance, effectively reducing energy consumption. The composite optical film prepared after UV curing has a peeling force performance greater than 200gf / in, which can meet the needs of the composite optical film industry. The purpose of this application is achieved through the following technical solutions, which specifically include the following components by weight:
[0006] Acrylate oligomer 20-40 parts
[0007] Polyurethane acrylate oligomer 10-30 parts
[0008] Epoxy acrylate oligomer 10-30 parts
[0009] Isobornyl acrylate 20-30 parts
[0010] Tetrahydrofuran acrylate 5-15 parts
[0011] 10-20 parts of cyclotrimethylolpropane formal acrylate;
[0012] The acrylate oligomer is prepared from the following components in parts by weight:
[0013] Butyl acrylate 30-50 parts
[0014] 10-30 parts of 2-ethylhexyl acrylate
[0015] 2-Hydroxyethyl Acrylate 10-30 parts
[0016] 5-15 parts of methacrylate
[0017] Acrylic acid 6-10 parts
[0018] 1-Hydroxycyclohexyl phenyl ketone 1-3 parts;
[0019] Wherein, the viscosity of the acrylate oligomer is in the range of 100-800 mPa·s.
[0020] In one embodiment, a photoinitiator is also included.
[0021] In one embodiment, the photoinitiator includes the following weight portions of a first photoinitiator and a second photoinitiator:
[0022] 2-5 parts of the first photoinitiator
[0023] The second photoinitiator 0.5-2 parts;
[0024] The first photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the second photoinitiator is 2,4,6-trimethylbenzoyl diphenoxyphosphine.
[0025] In one embodiment, a coupling agent is also included.
[0026] In one embodiment, the coupling agent includes the following weight parts of an isocyanate coupling agent and an epoxy coupling agent:
[0027] Isocyanate coupling agent 0.1-2 parts
[0028] Epoxy coupling agent 0.1-2 parts.
[0029] In one embodiment, the viscosity of the UV acrylic optical bonding glue is less than 500 mPa·s.
[0030] In addition, the present application also provides a method for preparing UV acrylic optical bonding glue, comprising:
[0031] The following parts by weight of acrylic acid monomer were added into a glass reactor in order, and stirred under the protection of nitrogen atmosphere:
[0032] Butyl acrylate 30-50 parts
[0033] 10-30 parts of 2-ethylhexyl acrylate
[0034] 2-Hydroxyethyl Acrylate 10-30 parts
[0035] 5-15 parts of methacrylate
[0036] Acrylic acid 6-10 parts
[0037] 1-Hydroxycyclohexyl phenyl ketone 1-3 parts;
[0038] After stirring evenly, UV light is irradiated to cause free radical polymerization reaction. The intensity of UV light is between 1mw / cm 2 -7mw / cm 2 The irradiation photopolymerization reaction time is adjusted to control the viscosity of the oligomer to be 100-800 mPa·s, thereby obtaining the target acrylate oligomer;
[0039] The following components in parts by weight were added into a glass reactor in sequence:
[0040] Acrylate oligomer 20-40 parts
[0041] Polyurethane acrylate oligomer 10-30 parts
[0042] Epoxy acrylate oligomer 10-30 parts
[0043] Isobornyl acrylate 20-30 parts
[0044] Tetrahydrofuran acrylate 5-15 parts
[0045] 10-20 parts of cyclotrimethylolpropane formal acrylate;
[0046] The UV acrylic optical bonding glue is obtained by shading, stirring and standing.
[0047] In one embodiment, the wavelength band of the ultraviolet radiation is 315-400nm.
[0048] The present application further provides a composite optical film, including a bonding adhesive layer and a prism layer, wherein the bonding adhesive layer is formed by the aforementioned UV acrylic optical bonding glue.
[0049] Compared with the prior art, the present application has the following beneficial effects: the UV acrylic optical bonding glue prepared by the present application is a mixture of three systems: acrylate oligomers, polyurethane oligomers, and epoxy oligomers, which satisfies the requirements that the UV acrylic optical bonding glue has both soft bonding performance and high tensile strength and bonding performance, and has low viscosity. It can be directly used in the composite optical film industry without dilution, reducing solvent pollution and manufacturing costs.
[0050] By adding two coupling agents, 3-isocyanatepropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane coupling agent, a chemical bonding force is formed between the coupling agent of the bonding adhesive layer and the surface of the prism layer at room temperature, and the bonding force is highly stable, so that the bonding adhesive has strong adhesion to the prism layer. When the bonding width is only 4μm, the room temperature peeling force can reach more than 200gf / in, and it still maintains a certain bonding performance under harsh conditions of high temperature and high humidity, which can meet the needs of a narrow bonding area to achieve strong bonding characteristics, thereby improving the bonding process yield of composite film products in the optical film industry.
[0051] The low-viscosity UV acrylic optical bonding glue prepared in the present application has a viscosity of less than 500mPa·s, and can be directly coated and photocured without solvent dilution, avoiding the problems of solvent pollution and waste of heat energy consumption. The peeling force performance after bonding is better than that of existing glues, and the peeling force of the prism layer can achieve a continuous high peeling force effect. In the high temperature and high humidity test of 65℃ / 95%RH, the peeling force can still maintain a peeling force strength of more than 50% after 1000 hours. The UV acrylic optical bonding glue of the present application is a low-viscosity solvent-free photocurable acrylic optical glue. The viscosity of the glue is lower than that of the same type of UV acrylic optical bonding glue on the market, with a viscosity of less than 500mPa·s. It can be used for direct coating production without the need to add organic solvents for dilution, reducing the cost price of optical film manufacturers and reducing organic solvent pollution and heat energy consumption in the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a schematic diagram of the structure of a composite optical film in one embodiment of the present application.
[0053] Explanation of reference numerals: 100, bonding adhesive layer; 200, prism layer; 300, substrate layer. DETAILED DESCRIPTION
[0054] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0055] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.
[0056] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0057] As a key link in display manufacturing, the preparation technology of composite optical films and the materials used, especially the performance of UV acrylic optical bonding glue, directly determine the image quality, brightness, durability and overall manufacturing cost of the display. Traditional UV acrylic optical bonding glue often has problems such as high viscosity, solvent dilution, high energy consumption and insufficient peeling force performance, which seriously restricts the development of the composite optical film industry.
[0058] In view of this, the present application proposes a new UV acrylic optical bonding glue solution, which not only has the characteristics of low viscosity and direct coating, but also has excellent soft bonding performance, high tensile strength and excellent peeling performance. In addition, the glue can be used without solvent, thus effectively avoiding the problem of heat energy consumption, which is in line with the current green and sustainable development concept. It has both soft bonding performance and high tensile strength and bonding performance, and has low viscosity. It can be directly used in the composite optical film industry without dilution. The UV acrylic optical bonding glue of the present application includes the following components by weight:
[0059] Acrylate oligomer 20-40 parts
[0060] Polyurethane acrylate oligomer 10-30 parts
[0061] Epoxy acrylate oligomer 10-30 parts
[0062] Isobornyl acrylate 20-30 parts
[0063] Tetrahydrofuran acrylate 5-15 parts
[0064] Cyclotrimethylolpropane formal acrylate 10-20 parts.
[0065] The UV acrylic optical bonding glue of the present application adopts a solution of mixing three systems including acrylate oligomers, polyurethane acrylate oligomers and epoxy acrylate oligomers. The bonding glue is given soft bonding properties, so that it can be tightly bonded to various complex optical film surfaces, while ensuring that the glue has a high tensile strength, effectively improving the overall strength and durability of the composite optical film. It should be noted that the acrylate oligomer here refers to an oligomer polymerized from monofunctional (meth) acrylic and / or (meth) acrylic ester monomers, which can be an oligomer polymerized from a single component or an oligomer polymerized from multiple components.
[0066] In the selection of acrylate oligomers, the present application further optimizes the ratio of each component, and successfully prepares a kind of acrylate oligomer system that has excellent fluidity and film-forming properties, and can ensure that the glue has ideal physical properties after curing by introducing raw materials such as butyl acrylate, isooctyl acrylate, 2-hydroxyethyl acrylate, methacrylate and acrylic acid. While maintaining a low viscosity, the bonding glue of the present application can be directly applied to the composite optical film industry without solvent dilution, reducing solvent pollution and manufacturing costs. In addition, the UV acrylic optical bonding glue of the present application further improves the comprehensive performance of the glue by introducing raw materials such as tetrahydrofuran acrylate and cyclotrimethylolpropane formal acrylate. The addition of these raw materials not only helps to improve the adhesion and peeling force of the glue, but also enables the glue to form a more compact and stable cross-linked structure during the curing process, thereby improving the heat resistance and weather resistance of the composite optical film. It should be noted that the UV acrylic optical bonding glue of the present application is limited to include the above components. Those skilled in the art know that additional additives can be added thereto as needed, and it is not strictly limited to being composed of only the above components. In addition, the bonding glue of the present application can be used without diluting the solution, but the application scenario of using solvents is not excluded. In the specific use process, UV acrylic optical bonding glue composed only of the above components is preferred.
[0067] Specifically, the acrylate oligomer is prepared from the following components in parts by weight:
[0068] Butyl acrylate 30-50 parts
[0069] 10-30 parts of 2-ethylhexyl acrylate
[0070] 2-Hydroxyethyl Acrylate 10-30 parts
[0071] 5-15 parts of methacrylate
[0072] Acrylic acid 6-10 parts
[0073] 1-Hydroxycyclohexyl phenyl ketone 1-3 parts.
[0074] Through experiments, it is found that the acrylate oligomer formed by the above components can make the UV acrylic optical bonding adhesive have a lower viscosity under the same processing flow (including mixing, stirring, standing and other steps). In addition, due to the addition of acrylic acid, the bonding performance of the UV acrylic optical bonding adhesive is improved. Specifically, it also includes a photoinitiator, and the photoinitiator includes the following weight parts of a first photoinitiator and a second photoinitiator:
[0075] 2-5 parts of the first photoinitiator
[0076] The second photoinitiator 0.5-2 parts;
[0077] The first photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the second photoinitiator is 2,4,6-trimethylbenzoyl diphenoxyphosphine.
[0078] A dual photoinitiator system consisting of the first photoinitiator 1-hydroxycyclohexyl phenyl ketone and the second photoinitiator 2,4,6-trimethylbenzoyl diphenylphosphine was added. This combination design not only makes full use of the complementarity of the two photoinitiators in the absorption spectrum, broadens the photocuring wavelength range of the glue, and enables the glue to achieve efficient curing under a wider range of lighting conditions, but also achieves fine control of the curing speed by adjusting the ratio of the two photoinitiators. By using two photoinitiators, the process requirements for the use of UV acrylic optical bonding glue can be reduced, and it can be applied to a variety of scenarios with higher universality.
[0079] Specifically, a coupling agent is also included, and the coupling agent includes the following weight parts of an isocyanate coupling agent and an epoxy coupling agent:
[0080] Isocyanate coupling agent 0.1-2 parts
[0081] Epoxy coupling agent 0.1-2 parts.
[0082] Isocyanate coupling agents and epoxy coupling agents are added to the bonding glue. With their unique chemical structures, these two coupling agents can interact strongly with the polar groups on the surface of the optical film and the polymer chains in the glue, respectively, thereby forming a strong chemical bond at the interface. This chemical bond not only improves the adhesion between the glue and the optical film, but also enhances the overall structural stability of the composite optical film, enabling it to withstand greater external impact and temperature changes without falling off or cracking. The addition of isocyanate coupling agents allows the glue to react with polar groups such as hydroxyl and amino groups on the surface of the optical film during the curing process to form stable urea bonds or carbamate bonds, thereby greatly improving the adhesion strength and durability of the interface. The epoxy coupling agent, on the other hand, undergoes a cross-linking reaction with the hydroxyl or amino groups in the glue through its epoxy group, further enhancing the bonding between the glue and the optical film, and improving the heat resistance and chemical corrosion resistance of the composite optical film. The weight ratio of isocyanate coupling agent to epoxy coupling agent is between 1:20-20:1, and further selected between 1:10-10:1. The comprehensive adhesion performance is improved by the appropriate ratio of the two coupling agents. Through experiments, it is found that when the two coupling agents are added at the same time, they have better adhesion performance. The isocyanate coupling agent and epoxy coupling agent with a close ratio in the coupling agent ratio can not only improve the adhesion at room temperature, but also ensure that it still has a high adhesion after 1000 hours under 65℃ / 95%RH conditions. Through further experiments, the weight ratio of the two coupling agents has relatively better performance and process controllability in the range of 1:4-4:1.
[0083] Specifically, the viscosity of the UV acrylic optical bonding glue is less than 500mPa·s. Through the components in the technical solution of the present application, UV acrylic optical bonding glue with lower viscosity can be achieved. When the viscosity is less than 500Pa·s, there is no need to use a solvent and it can be applicable to the current production line. In addition, since there is no solvent, there is no need to set up a solvent evaporation or drying processing unit in the production line or equipment, thereby reducing production costs and improving production efficiency.
[0084] In addition, the present application also provides a method for preparing UV acrylic optical bonding glue, comprising:
[0085] The following parts by weight of acrylic acid monomer were added into a glass reactor in order, and stirred under the protection of nitrogen atmosphere:
[0086] Butyl acrylate 30-50 parts
[0087] 10-30 parts of 2-ethylhexyl acrylate
[0088] 2-Hydroxyethyl Acrylate 10-30 parts
[0089] 5-15 parts of methacrylate
[0090] Acrylic acid 6-10 parts
[0091] 1-Hydroxycyclohexyl phenyl ketone 1-3 parts;
[0092] After stirring evenly, UV light is irradiated to cause free radical polymerization reaction. The intensity of UV light is between 1mw / cm 2 -7mw / cm 2 The irradiation photopolymerization reaction time is adjusted to control the viscosity of the oligomer to be 100-800 mPa·s, thereby obtaining the target acrylate oligomer;
[0093] The following components in parts by weight were added into a glass reactor in sequence:
[0094] Acrylate oligomer 20-40 parts
[0095] Polyurethane acrylate oligomer 10-30 parts
[0096] Epoxy acrylate oligomer 10-30 parts
[0097] Isobornyl acrylate 20-30 parts
[0098] Tetrahydrofuran acrylate 5-15 parts
[0099] 10-20 parts of cyclotrimethylolpropane formal acrylate;
[0100] The UV acrylic optical bonding glue is obtained by shading, stirring and standing.
[0101] Specifically, the wavelength band of the ultraviolet radiation is 315-400 nm, and the viscosity of the oligomer is controlled to be 100-800 mPa·s.
[0102] The specific method is as follows: the acrylic acid monomers of the above components are added into a glass reactor in parts by weight, and stirred for a certain period of time to achieve uniformity under the protection of nitrogen atmosphere, and then subjected to UV ultraviolet radiation to cause free radical polymerization reaction, wherein the wavelength of the ultraviolet radiation is 315-400nm, preferably 365nm, and the intensity of the ultraviolet light is between 1mw / cm 2 -7mw / cm 2 The viscosity of the oligomer is controlled to be between 100-800 mPa·s, and the target acrylate oligomer is finally obtained; the viscosity of the polyurethane acrylate oligomer is 6000-12000 mPa·s at 25°C, the solid content is 100%, the refractive index at 25°C is 1.49, and the functionality is 4; the viscosity of the epoxy acrylate is between 2000-10000 mPa·s at 25°C, the solid content is 100%, the refractive index at 25°C is 1.5, and the functionality is 2. The first photoinitiator is 1-hydroxycyclohexyl phenyl ketone, the second photoinitiator is 2,4,6-trimethylbenzoyldiphenoxyphosphine, the isocyanate coupling agent is one or more of 3-isocyanatepropyl triethoxysilane, 3-isocyanatepropyl trimethoxysilane, and 3-isocyanatepropyl methyldimethoxysilane, preferably 3-isocyanatepropyl triethoxysilane; the epoxy coupling agent is one or more of γ-glycidyloxypropyl trimethoxysilane, 3-(2,3-epoxypropyloxy)propyl methyldimethoxysilane, γ-glycidyloxypropyl triethoxysilane, β-(3, 4-epoxycyclohexyl)-ethyltriethoxysilane, β-(3, 4-epoxycyclohexyl)-ethyltrimethoxysilane, and 3-(2,3-epoxypropyloxy)propyl methyldiethoxysilane, preferably γ-glycidyloxypropyl trimethoxysilane. The above components were added into a glass reaction kettle in order according to weight portions, and the reaction was stirred for 2 hours under light shielding, and then allowed to stand for defoaming for 1 hour to obtain a low-viscosity solvent-free UV acrylic optical bonding glue, and the viscosity of the UV acrylic optical bonding glue was less than 500 mPa·s.
[0103] When preparing the composite optical film, low-viscosity UV acrylic optical bonding glue is poured into the glue tank of the coating machine, and the UV acrylic optical bonding glue is coated on the 125μm optical PET by using a 300-mesh micro-concave roller, and bonded with the isosceles triangle prism brightness enhancement film glue structure layer with a height of 35μm. The S roller (tension roller) method is used to control the effective bonding width of the optical bonding glue layer 100 to the prism layer 200 to be 2-8-μm, and then UV high-pressure curing is performed to effectively bond the bonding glue layer 100 and the prism layer 200. The prism layer 200 is formed by UV acrylic glue using an isosceles triangle structure copper mold roller with a height of 35μm, and then cured. The thickness of the optical film PET is between 25-500μm, preferably 125μm. The glue of the prism layer 200 is purchased from MN-Tech Company of South Korea with a grade of MR440BH; the pressure energy of the prism structure glue layer molding is 30-200mj / cm 2 Between, preferably 90mj / cm 2 , high pressure curing energy after lamination is 800-3000mj / cm 2 Between, preferably 2000 mj / cm 2 The effective bonding width of the optical bonding adhesive layer 100 and the prism layer 200 is 4 μm, and a composite optical film product is obtained.
[0104] See also Figure 1 , Figure 1 : is a schematic diagram of the structure of a composite optical film in an embodiment of the present application. The present application further provides a composite optical film, including a bonding adhesive layer 100 and a prism layer 200, wherein the bonding adhesive layer 100 is formed by the aforementioned UV acrylic optical bonding glue. The composite optical film also includes a substrate layer 300, which includes a substrate layer 300 that cooperates with the bonding adhesive layer 100 and a substrate layer 300 that cooperates with the prism layer 200. The effective bonding width of the bonding adhesive layer 100 and the prism layer is 2-8 μm, and preferably the effective bonding width is 4 μm.
[0105] Specific embodiments: Some specific implementation methods will be further introduced below to further explain the technical solution of the present application in detail.
[0106] Example 1
[0107] This embodiment prepares a low-viscosity UV acrylic optical bonding glue, which includes the following components in parts by weight:
[0108] 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 0.1 parts of 3-isocyanatepropyltriethoxysilane, and 0 parts of γ-glycidyloxypropyltrimethoxysilane.
[0109] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 40 parts of butyl acrylate, 20 parts of isooctyl acrylate, 20 parts of 2-hydroxyethyl acrylate, 10 parts of decyl methacrylate, 8 parts of acrylic acid, and 2 parts of 1-hydroxycyclohexyl phenyl ketone.
[0110] The acrylic monomers of the above components were added into a glass reactor in parts by weight, and stirred for a certain period of time to achieve uniformity under the protection of nitrogen atmosphere, and then subjected to UV ultraviolet radiation to cause free radical polymerization reaction. The wavelength of ultraviolet radiation was 365nm, and the intensity of ultraviolet light was between 1mw / cm 2 -7mw / cm 2 The viscosity of the oligomer is controlled to be 100-800 mPa·s, and the target acrylate oligomer is finally obtained; each component is added to a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue, and the optical bonding glue is coated on a 125μm optical PET using a 300-mesh micro-concave roller, and the thickness of the optical bonding glue layer is 3μm, and then bonded with the formed prism layer, and the effective bonding width of the prism layer and the bonding glue layer is controlled to be 4μm, and finally high-pressure curing is performed to obtain a composite optical film product, wherein the prism layer is formed by a copper mold with an isosceles triangle prism structure with a height of 35μm, and then medium-pressure curing and coating is obtained, and the medium-pressure curing energy is 90mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea, and the high-pressure curing energy after bonding is 2000 mj / cm 2 .
[0111] Example 2
[0112] This embodiment prepares a low-viscosity UV acrylic optical bonding glue, which includes the following components in parts by weight:
[0113] 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyl diphenyl oxide, 1 part of 3-isocyanate propyl triethoxy silane, and 0 parts of γ-glycidyl ether oxygen propyl trimethoxy silane. The acrylate oligomer component is consistent with that in Example 1.
[0114] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0115] Example 3
[0116] The present embodiment prepares a low-viscosity UV acrylic optical bonding glue, including the following components in parts by weight: 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 1.5 parts of 3-isocyanatepropyltriethoxysilane, and 0 parts of γ-glycidyloxypropyltrimethoxysilane.
[0117] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 30 parts of butyl acrylate, 10 parts of isooctyl acrylate, 10 parts of 2-hydroxyethyl acrylate, 5 parts of decyl methacrylate, 6 parts of acrylic acid, and 1 part of 1-hydroxycyclohexyl phenyl ketone.
[0118] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0119] Example 4
[0120] The present embodiment prepares a low-viscosity UV acrylic optical bonding glue, including the following components in parts by weight: 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 2 parts of 3-isocyanatepropyltriethoxysilane, and 0 parts of γ-glycidyloxypropyltrimethoxysilane.
[0121] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 50 parts of butyl acrylate, 30 parts of isooctyl acrylate, 30 parts of 2-hydroxyethyl acrylate, 15 parts of decyl methacrylate, 10 parts of acrylic acid, and 3 parts of 1-hydroxycyclohexyl phenyl ketone.
[0122] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0123] Example 5
[0124] In this embodiment, a low-viscosity UV acrylic optical bonding glue is prepared, including the following components in parts by weight: 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 0.5 parts of 3-isocyanatepropyltriethoxysilane, and 0.5 parts of γ-glycidyloxypropyltrimethoxysilane.
[0125] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 30 parts of butyl acrylate, 30 parts of isooctyl acrylate, 10 parts of 2-hydroxyethyl acrylate, 15 parts of decyl methacrylate, 6 parts of acrylic acid, and 3 parts of 1-hydroxycyclohexyl phenyl ketone.
[0126] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0127] Example 6
[0128] The present embodiment prepares a low-viscosity UV acrylic optical bonding glue, including the following components in parts by weight: 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 1 part of 3-isocyanatepropyltriethoxysilane, and 1 part of γ-glycidyloxypropyltrimethoxysilane.
[0129] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 50 parts of butyl acrylate, 10 parts of isooctyl acrylate, 30 parts of 2-hydroxyethyl acrylate, 5 parts of decyl methacrylate, 10 parts of acrylic acid, and 1 part of 1-hydroxycyclohexyl phenyl ketone.
[0130] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0131] Example 7
[0132] In this embodiment, a low-viscosity UV acrylic optical bonding glue is prepared, including the following components in parts by weight: 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 2 parts of 3-isocyanatepropyltriethoxysilane, and 2 parts of γ-glycidyloxypropyltrimethoxysilane.
[0133] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 40 parts of butyl acrylate, 30 parts of isooctyl acrylate, 20 parts of 2-hydroxyethyl acrylate, 5 parts of decyl methacrylate, 8 parts of acrylic acid, and 3 parts of 1-hydroxycyclohexyl phenyl ketone.
[0134] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0135] Example 8
[0136] The present embodiment prepares a low-viscosity UV acrylic optical bonding glue, including the following components in parts by weight: 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 0 parts of 3-isocyanatepropyltriethoxysilane, and 2 parts of γ-glycidyloxypropyltrimethoxysilane.
[0137] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 45 parts of butyl acrylate, 25 parts of isooctyl acrylate, 15 parts of 2-hydroxyethyl acrylate, 12 parts of decyl methacrylate, 8 parts of acrylic acid, and 2 parts of 1-hydroxycyclohexyl phenyl ketone.
[0138] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0139] Example 9
[0140] The present embodiment prepares a low-viscosity UV acrylic optical bonding glue, including the following components in parts by weight: 40 parts of acrylate oligomer, 30 parts of polyurethane acrylate oligomer, 30 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 1 part of 3-isocyanatepropyltriethoxysilane, and 1 part of γ-glycidyloxypropyltrimethoxysilane.
[0141] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 30 parts of butyl acrylate, 30 parts of isooctyl acrylate, 30 parts of 2-hydroxyethyl acrylate, 15 parts of decyl methacrylate, 10 parts of acrylic acid, and 3 parts of 1-hydroxycyclohexyl phenyl ketone.
[0142] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0143] Comparative Example 1
[0144] The present embodiment prepares a low-viscosity UV acrylic optical bonding glue, including the following components in parts by weight: 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 0 parts of 3-isocyanatepropyltriethoxysilane, and 0 parts of γ-glycidyloxypropyltrimethoxysilane.
[0145] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 40 parts of butyl acrylate, 20 parts of isooctyl acrylate, 20 parts of 2-hydroxyethyl acrylate, 10 parts of decyl methacrylate, 8 parts of acrylic acid, and 2 parts of 1-hydroxycyclohexyl phenyl ketone.
[0146] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0147] Comparative Example 2
[0148] In this embodiment, a low-viscosity UV acrylic optical bonding glue is prepared, including the following components in parts by weight: 30 parts of acrylate oligomer, 0 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 1 part of 3-isocyanatepropyltriethoxysilane, and 1 part of γ-glycidyloxypropyltrimethoxysilane.
[0149] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 40 parts of butyl acrylate, 20 parts of isooctyl acrylate, 20 parts of 2-hydroxyethyl acrylate, 10 parts of decyl methacrylate, 8 parts of acrylic acid, and 2 parts of 1-hydroxycyclohexyl phenyl ketone.
[0150] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0151] Comparative Example 3
[0152] The present embodiment prepares a low-viscosity UV acrylic optical bonding glue, including the following components in parts by weight: 30 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 0 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 1 part of 3-isocyanatepropyltriethoxysilane, and 1 part of γ-glycidyloxypropyltrimethoxysilane.
[0153] The acrylate oligomer is prepared by polymerizing the following acrylic monomers: 40 parts of butyl acrylate, 20 parts of isooctyl acrylate, 20 parts of 2-hydroxyethyl acrylate, 10 parts of decyl methacrylate, 8 parts of acrylic acid, and 2 parts of 1-hydroxycyclohexyl phenyl ketone.
[0154] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0155] Comparative Example 4
[0156] The present embodiment prepares a low-viscosity UV acrylic optical bonding glue, including the following components in parts by weight: 0 parts of acrylate oligomer, 20 parts of polyurethane acrylate oligomer, 15 parts of epoxy acrylate oligomer, 20 parts of isobornyl acrylate, 10 parts of tetrahydrofuran acrylate, 15 parts of cyclotrimethylolpropane formal acrylate, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 1 part of 2,4,6-trimethylbenzoyldiphenoxyphosphine, 1 part of 3-isocyanatepropyltriethoxysilane, and 1 part of γ-glycidyloxypropyltrimethoxysilane.
[0157] The components were added into a glass reactor in parts by weight, stirred for 2 hours in a dark place, and then allowed to stand for defoaming to obtain a low-viscosity UV acrylic optical bonding glue. A 300-mesh micro-concave roller was used to coat the UV acrylic optical bonding glue on a 125 μm optical PET. The thickness of the optical bonding glue layer was 3 μm. The prism layer was then bonded to the formed prism layer. The effective bonding width of the prism layer and the bonding glue layer was controlled to be 4 μm. Finally, high-pressure curing was performed to obtain a composite optical film product. The prism layer was formed by a copper mold with an isosceles triangle prism structure with a height of 35 μm and then coated with medium-pressure curing. The medium-pressure curing energy was 90 mj / cm 2 The glue type is MR440BH from MN-Tech of South Korea. The high-pressure curing energy after bonding is 2000mj / cm 2 .
[0158] Test content and results. The following tests are conducted on the viscosity, bonding width, room temperature bonding strength and post-RA bonding strength of each implementation method. Among them, the viscosity test value of UV acrylic optical glue is the average value of three values tested by a viscosity testing instrument. The viscometer model is the Bo Le Fei DV2T model viscometer. The prism layer bonding width test value is tested by a metallographic microscope, focusing on the bonding position to test the width value. The model of the metallographic microscope is Jiangnan Yongxin Optical Company MV5000. The room temperature bonding strength test value is the average value of three values when the composite optical film product is cut into a width of 25.4mm and the optical bonding layer is tested by a tensile machine at room temperature. The speed of the tensile machine is 300mm / min, and the tensile machine is the KJ-1065 model of Guangdong Kejian Instrument Company. The post-RA bonding strength is the peeling strength of the bonding layer to the prism layer after the composite optical film product is placed in 65℃ / 95%RH for 1000 hours, which is the average value of three values.
[0159] The test results are summarized in Table 1.
[0160] Table 1 Summary of test results of various embodiments
[0161]
[0162] It can be seen from the above test results that the room temperature peeling force and the post-RA peeling force in Examples 1-9 are greatly improved compared with those in Comparative Examples 1-4, and the low-viscosity solvent-free photocurable acrylic bonding glue of the present application has a lower viscosity than the same type of acrylic optical bonding glue on the market, and the viscosity is less than 500mPa·s, and can be used for direct coating production without the need to add organic solvents for dilution.
[0163] The UV acrylic optical bonding glue of the present application contains two types of coupling agents. Under normal temperature conditions, the isocyanate coupling agent 3-isocyanatepropyl triethoxysilane enables the UV acrylic optical bonding glue to have a strong bonding effect with the prism adhesive layer, and the epoxy coupling agent γ-glycidyl ether oxypropyl trimethoxysilane ensures the long-term stability of the bonding force of the bonding glue to the prism layer; at the same time, under high temperature and high humidity environments, the bonding force between the bonding adhesive layer and the prism adhesive layer is improved, and the bonding force between the bonding adhesive layer and the PET layer is improved, which will not cause the bonding at high temperature. Under high humidity environment, the laminating adhesive layer and PET peeled off, or the bonding strength between the laminating adhesive layer and the prism adhesive layer dropped significantly. The room temperature peeling force of the laminating adhesive without adding two coupling agents to the prism layer was below 150gf, and the peeling force decreased by more than 80% after 1000 hours under 65℃ / 95%RH conditions. The room temperature peeling force of the laminating adhesive with two types of coupling agents to the prism layer was above 200gf / in, and the peeling force value only decreased by less than 50% after 1000 hours under 65℃ / 95%RH conditions.
[0164] From the foregoing, it can be seen that the present application provides a UV acrylic optical bonding glue specially designed for the composite optical film industry, which has excellent soft bonding performance, high tensile strength and low viscosity characteristics. The composition formula includes acrylate oligomers, polyurethane acrylate oligomers, epoxy acrylate oligomers, isobornyl acrylate, tetrahydrofuran acrylate and cyclotrimethylolpropane formal acrylate and other ingredients. It can be directly applied without solvent dilution to achieve the required coating thickness and appearance quality, thereby effectively reducing energy consumption.
[0165] The UV acrylic optical bonding glue of the present application has a low viscosity of less than 500mPa·s and can be directly used in the preparation process of the composite optical film without the need for an additional solvent dilution step. After UV curing, the prepared composite optical film exhibits excellent anti-peeling properties, with a peeling force greater than 200gf / in, which fully meets the industry's demand for high-strength bonding. In addition, the glue formula of the present application also contains isocyanate coupling agents and epoxy coupling agents, which can form stable chemical bonding forces with the surface of the prism layer at room temperature, and can achieve strong bonding effects even in a narrow bonding area, thereby improving the bonding process yield of composite film products.
[0166] Compared with the prior art, the UV acrylic optical bonding glue of the present application not only simplifies the production process and reduces manufacturing costs, but also reduces the use of organic solvents and heat energy consumption, which is in line with the green and environmentally friendly production concept. At the same time, the peel strength of the glue in a high temperature and high humidity environment can still be maintained at more than 50%, ensuring the stability and durability of the composite optical film in harsh environments. Therefore, the UV acrylic optical bonding glue of the present application provides an efficient, environmentally friendly and excellent performance solution for the composite optical film industry.
[0167] The above is only a specific implementation of the present application, and any improvements made based on the concept of the present application are deemed to be within the protection scope of the present application.
Claims
1. A UV acrylic optical bonding glue, characterized in that: The composition comprises the following components in parts by weight: Acrylate oligomer 20-40 parts Polyurethane acrylate oligomer 10-30 parts Epoxy acrylate oligomer 10-30 parts Isobornyl acrylate 20-30 parts Tetrahydrofuran acrylate 5-15 parts Cyclotrimethylolpropane formal acrylate 10-20 parts Isocyanate coupling agent 0.1-2 parts 0.1-2 parts of epoxy coupling agent; The acrylate oligomer is prepared from the following components in parts by weight: Butyl acrylate 30 -50 parts 10-30 parts of 2-ethylhexyl acrylate 2-Hydroxyethyl Acrylate 10-30 parts 5-15 parts of methacrylate Acrylic acid 6-10 parts 1-Hydroxycyclohexyl phenyl ketone 1-3 parts; Wherein, the viscosity of the acrylate oligomer is in the range of 100-800 mPa·s.
2. The UV acrylic optical bonding glue according to claim 1, characterized in that: Also included are photoinitiators.
3. The UV acrylic optical bonding glue according to claim 2, characterized in that: The photoinitiator comprises the following weight parts of a first photoinitiator and a second photoinitiator: 2-5 parts of the first photoinitiator 0.5-2 parts of the second photoinitiator; The first photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the second photoinitiator is 2,4,6-trimethylbenzoyl diphenoxyphosphine.
4. The UV acrylic optical bonding glue according to claim 1, characterized in that: The viscosity of UV acrylic optical bonding glue is less than 500mPa·s.
5. A method for preparing UV acrylic optical bonding glue, characterized in that: include: The following parts by weight of acrylic acid monomer were added into a glass reactor in order, and stirred under the protection of nitrogen atmosphere: Butyl acrylate 30 -50 parts 10-30 parts of 2-ethylhexyl acrylate 2-Hydroxyethyl Acrylate 10-30 parts 5-15 parts of methacrylate Acrylic acid 6-10 parts 1-Hydroxycyclohexyl phenyl ketone 1-3 parts; After stirring evenly, UV light is irradiated to cause free radical polymerization reaction. The intensity of UV light is between 1mw / cm 2 -7mw / cm 2 Adjusting the radiation photopolymerization reaction time to control the viscosity of the oligomer within the range of 100-800 mPa·s to obtain the target acrylate oligomer; The following components in parts by weight were added into a glass reactor in sequence: Acrylate oligomer 20-40 parts Polyurethane acrylate oligomer 10-30 parts Epoxy acrylate oligomer 10-30 parts Isobornyl acrylate 20-30 parts Tetrahydrofuran acrylate 5-15 parts Cyclotrimethylolpropane formal acrylate 10-20 parts Isocyanate coupling agent 0.1-2 parts 0.1-2 parts of epoxy coupling agent; The UV acrylic optical bonding glue is obtained by shading, stirring and standing.
6. The method for preparing the UV acrylic optical bonding glue according to claim 5, characterized in that: The wavelength of the ultraviolet light is 315-400nm.
7. A composite optical film, characterized in that: It comprises a bonding adhesive layer and a prism layer, wherein the bonding adhesive layer is formed by the UV acrylic optical bonding adhesive according to any one of claims 1 to 4.
Citation Information
Patent Citations
OCA optical adhesive, preparation method and application thereof, and optical film based on OCA optical adhesive
CN112980338A
OCA optical glue for curved screen, glue film and preparation method of OCA optical glue
CN115124928A